PENINGKATAN PRESTASI BELAJAR MATEMATIKA SISWA DENGAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM INVESTIGATION SMP NEGERI 2 CEPER KLATEN - Aji Permana Putra (Intersections, 2020)
The purpose of this class action research is to (1) improve students' mathematics learning achievement through the Group Investigation learning model in class VII F SMPN 2 Ceper, Ceper District, Klaten Regency 2017/2018 Academic Year. (2) Describe how to overcome the constraints of applying the Group Investigation learning model to improve mathematics learning achievement of class VII F SMPN 2 Ceper. Based on the results of the study it can be concluded: (1) The application of the Group Investigation learning model can improve the learning achievement of grade VII F SMPN 2 Ceper, which is indicated by: students of class VII F as many as 32 students have increased learning achievement that is before action only 53.1% of students study completely, after the action becomes 100%. How to overcome constraints, namely the teacher must be skilled in applying Group Investigation learning model is: a) reviewing the concepts and basic competencies that students will learn, b) forming heterogeneous study groups both in terms of ability, gender, religion, tribes etc., c) prepare everything about learning as well as possible so that when learning runs smoothly, d) minimize the number of group members so that learning takes place effectively with no passive group members or playing alone during group discussions, e) giving gifts at the best group presentations